Penerapan Metode Pembelajaran Role Playing (Bermain Peran) Untuk Meningkatkan Keterampilan Sosial Siswa Kelas V Di SDN Pecakur - Afiaty Dewi, Arini; Siti Okah Hujatunnufus; Andini Piatni; Sastra Wijaya (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
ABSTRACT This research aims to determine the effect of using the role playing learning method on students' social skills in studying social studies material. The population used by the researcher was female elementary school students in class V at SDN Pecakur Ds. Attack, District. Pontang, Serang Regency, Province. Banten in the 2023/2024 academic year. This research uses classroom action research (PTK). Based on the results of research before using the role playing learning method, the social skills of class V students when the pre-cycle assessment was carried out, the average student score was 18.23%. This score was in the low category. This low score could occur because of the low social skills possessed by the students. students also lack interest in studying social studies. This can happen because the teacher is inaccurate in implementing the model with the teaching material in social studies lessons, whereas after using the active learning model in the form of role playing and carrying out cycle 1, the average student score has increased to 45.68% and in cycle II students achieved mastery in social skills at 81.77% and this is included in the high improvement category. In this case, the application of the role playing learning method in social studies subjects is said to be able to improve social skills for class V students at SDN Pecakur. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh dari penggunaan metode pembelajaran Role playing dalam keterampilan sosial peserta didik dalam mempelajari materi IPS, populasi yang dilakukan peneliti merupkaan peserta didik siswi sekolah dasar kelas V di SDN Pecakur Ds. Keserangan, Kec. Pontang Kabupaten Serang Prov. Banten pada Tahun ajaran 2023/2024. Penelitian ini menggunkan penelitian tindak kelas (PTK). Berdasarkan hasil penelitian sebelum menggunakan metode pembelajaran Role playing keterampilan sosial peserta didik kelas V ketika dilakukan Penilaian Pra siklus rata rata nilai peserta didik sebesar 18,23% nilai ini masuk dalam kategori rendah, perolehan nilai rendah ini bisa terjadi karna rendahnya keterampilan sosial yang dimiliki oleh peserta didik juga kurangnya rasa tertarik dalam mempelajari IPS hal ini bisa terjadi karna ketidak tepatan guru dalam mengimplementasikan model dengan materi ajar yang ada di Pelajaran IPS, sedangkan setelah digunakannya model pembelajaran aktif berupa Role Playing dan dilakukannya siklus 1 rata rata nilai peserta didik mengalami peningkatan menjadi 45,68% dan pada siklus II peserta didik mencapai ketuntasan dalam keterampilan sosial sebesar 81,77% dan ini termasuk kedalam kategori peningkatan tinggi. Dalam hal ini penerapan metode pembelajaran Role playing pada mata pelajaran IPS dikatakan mampu meningkatkan keterampilan sosial bagi peserta didik kelas V di SDN Pecakur.